2021
DOI: 10.1149/1945-7111/abde80
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Phase Purity and Crystallinity on Chloramphenicol Sensing Performance of CuCo2O4/CuFe2O4-based Electrochemical Nanosensors

Abstract: For the first time, the influences of phase purity and crystallinity on the electrochemical and electrocatalytic properties of CuCo2O4 (CCO) and CuFe2O4 (CFO)-based electrochemical sensors for the detection of chloramphenicol (CAP) are reported. A series of CCO and CFO nanoparticles were prepared by a modified coprecipitation method and then annealed at different temperatures under air (400 °C, 600 °C, 800 °C, and 1000 °C). Surface morphology, the evolution of the crystallite size, and crystalline phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…This is consistent with many previous reports for the electrochemical reduction process of CAP occurring at the electrode surface. 38,[43][44][45][46] In both cases, with and without the presence of CAP, the reduction peak at around À0.4 V to À0.5 V could be ascribed to the irreversible reduction of residual hydroxyl or other functional groups on the commercial SPE surface. 46 R-NO 2 + 4e…”
Section: Electrochemical Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with many previous reports for the electrochemical reduction process of CAP occurring at the electrode surface. 38,[43][44][45][46] In both cases, with and without the presence of CAP, the reduction peak at around À0.4 V to À0.5 V could be ascribed to the irreversible reduction of residual hydroxyl or other functional groups on the commercial SPE surface. 46 R-NO 2 + 4e…”
Section: Electrochemical Investigationsmentioning
confidence: 99%
“…38,[43][44][45][46] In both cases, with and without the presence of CAP, the reduction peak at around À0.4 V to À0.5 V could be ascribed to the irreversible reduction of residual hydroxyl or other functional groups on the commercial SPE surface. 46 R-NO 2 + 4e…”
Section: Electrochemical Investigationsmentioning
confidence: 99%
“…Furthermore, it was observed that the reduction potential slightly shifted to the more negative direction along with the increased 4-NP concentration, which is attributed to the involvement of protons and the change in the pH value around the electrode interface. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was observed that the reduction potential slightly shied to the more negative direction along with the increased 4-NP concentration, which is attributed to the involvement of protons and the change in the pH value around the electrode interface. 17 In comparison with two other modied electrodes, the GT-AgNPs exhibited the highest electrochemical sensitivity up to 1.25 mA mM À1 cm À2 along with the lowest detection limit of 4-NP of about 0.42 mM in the wider linear range from 0.5 to 50 mM. The electrochemical sensitivity of MP-AgNPs was calculated to be 1.04 mA mM À1 cm À2 with a detection limit of about 0.63 mM in the concentration linear range from 1 to 50 mM.…”
Section: Optimization Of the 4-np Determination Conditionsmentioning
confidence: 99%
See 1 more Smart Citation